Mixed oligosaccharides-induced changes in bacterial assembly during cucumber (Cucumis sativus L.) growth - Wang, Qiushui; Zhou, Xin; Liu, Yue; Han, Yan; Zuo, Jia; Deng, Jie; Yuan, Liyan; Gao, Lijuan; Bai, Wenbo (Frontiers in Microbiology, 2023)
The application of oligosaccharides can promote plant growth by increasing photosynthesis or inducing plant innate immunity. However, the mechanisms by which oligosaccharides affect bacterial community diversity and abundance remain unclear. In this study, a mixed oligosaccharide was applied to the growth of cucumbers. The findings of the present study suggest that the application of MixOS has significant effects on the bacterial communities in the phyllosphere, rhizosphere, and bulk soil of cucumber plants. The treatment with MixOS resulted in delayed senescence of leaves, well-developed roots, and higher fruit production. The bacterial diversity and composition varied among the different ecological niches, and MixOS application caused significant shifts in the bacterial microbiome composition, particularly in the phyllosphere. Moreover, mixed oligosaccharides increased the abundance of potential growth-promoting bacteria such as Methylorubrum spp. and Lechevalieria spp., and more zOTUs were shared between the WM and MixOS treatments. Furthermore, the bacterial co-occurrence network analysis suggested that the modularity of the phyllosphere networks was the highest among all samples. The bacterial co-occurrence networks were altered because of the application of MixOS, indicating a greater complexity of the bacterial interactions in the rhizosphere and bulk soil. These findings suggest that mixed oligosaccharides has the potential to improve plant growth and yield by modulating the bacterial communities within and outside the plants and could provide a theoretical basis for future agricultural production.